2012
DOI: 10.1038/emboj.2012.236
|View full text |Cite
|
Sign up to set email alerts
|

AATF/Che-1 acts as a phosphorylation-dependent molecular modulator to repress p53-driven apoptosis

Abstract: Following genotoxic stress, cells activate a complex signalling network to arrest the cell cycle and initiate DNA repair or apoptosis. The tumour suppressor p53 lies at the heart of this DNA damage response. However, it remains incompletely understood, which signalling molecules dictate the choice between these different cellular outcomes. Here, we identify the transcriptional regulator apoptosis‐antagonizing transcription factor (AATF)/Che‐1 as a critical regulator of the cellular outcome of the p53 response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 35 publications
2
86
1
10
Order By: Relevance
“…Accumulating evidence reveals that in response to several cellular stresses, Che-1 is subjected to post-translational modifications that regulate its functions and localization (11,13). Although we observed that ATM/ATR and Chk2 are not involved in Che-1 centrosomal localization, we cannot exclude that other modifications are responsible for this localization or for its removal from this structure.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Accumulating evidence reveals that in response to several cellular stresses, Che-1 is subjected to post-translational modifications that regulate its functions and localization (11,13). Although we observed that ATM/ATR and Chk2 are not involved in Che-1 centrosomal localization, we cannot exclude that other modifications are responsible for this localization or for its removal from this structure.…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, in response to DNA damage, ATM-Chk2-phosphorylated Che-1 relocates to the TP53 promoter, activating its transcription and, consequently, that of several p53 target genes (11). It is noteworthy that Che-1 inhibition intensifies the cytotoxicity of DNA-damaging anticancer drugs, in such way reverting the chemoresistance of several tumor cell lines (11)(12)(13). Consistent with these findings, Che-1 depletion strongly decreases mutant p53 expression in human cancer cells, activates DNA damage checkpoint, and induces p73 transcription and apoptosis in these cells (14).…”
mentioning
confidence: 99%
“…45 Höpker and colleagues recently reported data corroborating these observations, showing an enhanced stability of DNA damage-induced cell cycle checkpoints upon overexpression of exogenous AATF. 47 These observations suggest that the effects of AATF overexpression depend at least partially on the activation status of the DDR network with AATF promoting cell cycle progression in the absence of DNA damage and enforcing a cell cycle arrest in response to genotoxic stress. These contrasting effects of AATF signaling correlate with distinct promoter binding of AATF in the different scenarios.…”
Section: The Tumor Suppressor P53 Serves As a Critical Signaling Hub mentioning
confidence: 90%
“…AATF was also shown to be a functional antagonist of cell-death inducer (NRAGE) during neuronal development, because its ectopic expression completely reverted NRAGE-induced cell death [1]. Recently, a new dimension was added to the belief that cell-cycle regulators are crucial for cell death by the finding which revealed that AATF had inherent capacity to put brakes on p53-driven apoptosis by binding to the PISMA, BAX and BAK promoters to repress the DNA damageinduced expression of these pro-apoptotic p53 target genes [27]. Strangely, AATF was found to be required for sustaining mutant p53 expression in several cancer cell lines and AATF depletion by siRNA was also accompanied by apoptosis in vitro and in vivo [1], thereby underlining the importance of AATF in survival of cells expressing mutant p53.…”
Section: Aatf Interactome and Cell Decisionmentioning
confidence: 99%